Pro‐inflammatory cytokines as emerging molecular determinants in cardiolaminopathies. Issue 23 (12th November 2021) - Gerbino, Andrea; Forleo, Cinzia; Milano, Serena; Piccapane, Francesca; Procino, Giuseppe; Pepe, Martino; Piccolo, Mara; Guida, Piero; Resta, Nicoletta; Favale, Stefano; Svelto, Maria; Carmosino, Monica
Abstract: Mutations in Lamin A/C gene ( lmna ) cause a wide spectrum of cardiolaminopathies strictly associated with significant deterioration of the electrical and contractile function of the heart. Despite the continuous flow of biomedical evidence, linking cardiac inflammation to heart remodelling in patients harbouring lmna mutations is puzzling. Therefore, we profiled 30 serum cytokines/chemokines in patients belonging to four different families carrying pathogenic lmna mutations segregating with cardiac phenotypes at different stages of severity ( n = 19) and in healthy subjects ( n = 11). Regardless lmna mutation subtype, high levels of circulating granulocyte colony‐stimulating factor (G‐CSF) and interleukin 6 (IL‐6) were found in all affected patients' sera. In addition, elevated levels of Interleukins (IL) IL‐1Ra, IL‐1β IL‐4, IL‐5 and IL‐8 and the granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) were measured in a large subset of patients associated with more aggressive clinical manifestations. Finally, the expression of the pro‐inflammatory 70 kDa heat shock protein (Hsp70) was significantly increased in serum exosomes of patients harbouring the lmna mutation associated with the more severe phenotype. Overall, the identification of patient subsets with overactive or dysregulated myocardial inflammatory responses could represent an innovative diagnostic, prognostic and therapeutic tool against Lamin A/C cardiomyopathies.